On demand delivery of ionic drugs from electro-responsive CNT hybrid films. Issue 56 (19th June 2015) - Curcio, M.; Spizzirri, U. G.; Cirillo, G.; Vittorio, O.; Picci, N.; Nicoletta, F. P.; Iemma, F.; Hampel, S.
<x xml:space="preserve">Abstract</x> Electro responsive hybrid hydrogel films able to precisely modulate the release of drugs as a function of their net charge.